Yoga in Transition: Exploring the Rise of Yoga in Peacebuilding. (1st August 2018) - Lefurgey, Mayme
Abstract : This article draws connections between the complexities of modern postural yoga practices and global peacebuilding efforts, exploring both tensions and possibilities. First, the article engages key yogic texts-such as Patañjali's Yogaśāstra, which demonstrates how yoga is historically rooted in social justice work and peacebuilding-in order to link yoga philosophy and peacebuilding theories. This is followed by an analysis of contemporary practice-based examples, which consider the theoretical tools of elicitive peacework and transrational peace research. Through an exploration of yoga as elicitive peacebuilding and conflict transformation, this article considers if yoga has the potential to shift societal notions of peacebuilding and questions the implications of this for peace theory and practice.